Optimising Rigor in Focus Group Analysis: Using Content/Thematic and Form/Structural Approaches to Understand British Somali's Experiences of Policing in London. - Ahmed, Anya; Quraishi, Muzammil; Abdillahi, Asha (International Social Science Review, 2017)
The article talks about focus groups that are meant for conducting group discussions and to understand the gravity of a certain issue. A focus group data is presented on young British Somali men's individual and shared experiences of policing in the London Borough of Camden. It states that the Black and Minority Ethnic (BME) populations are a subject that casts them as suspect population.